Educação ambiental entre a cartografia da lei e a formação do sujeito ecológico: esperança e desejo - Velho, Leonardo Vinicius Lima (2025)
This study discusses the path capable of fshaping the ecological subject beyond environmental potetion laws, with the aim of effectively protecting the environment. In this context, important concepts are used to foster dialogue and construct a unified sense of presservation. The concepts of eco-citizenship by Luís Alberto Warat and Buen Vivir by Alberto Acosta, transcend environmental protection laws and are analyzed through the metaphor of a map, using cartography as a tool construction, intertwining Ecology, Citizenship and Desire – Idea, Critical – transformative Commitment, and Hope. Seeking a right to the future and positioning the individual as a citizen-human, this study adresses the following question: What is the path capable of going beyond environmental protection laws, contributing to environmental protection and impact reduction while fostering citizens awareness of preservation? Thus, the central objective of the resarch is to investigate how this path surpasses environmental laws and becomes a means for shaping a responsible citizen as na integral parto f their environment. The specifiic objectives are, (I) to unveil the main elements of citizenship and Eco-citizenship; (II) to examine seven environmental protection laws through a cartography approach, considering historical contexto, legal text, and practical application. Finally, to assess the concept of Buen Vivir and the role of environmental education, considering the relationship between norm and anti-norm. Moreover, this study is relates to the research line “Rights of Sociobiodiversiy and Susteinability” within the Graduate Program in law at the Federal University of Santa Maria. The study concludes that environmental education is the primary measure for shapig individuals as integral parts of their surroundings. When citizens engage in environmental education practices based on the triado of knowledge-values-political participation, they promote autonomy, critical awakening of environmental issues, engagement, and the socio-cultural-economic contextualization of these issues, ultimately leading to the emancipation of the subject as parto f the environment they inhabit